Nanoparticles as Potential Novel Therapies for Urinary Tract Infections - Sánchez, Sofía V.; Navarro, Nicolás; Catalán-Figueroa, Johanna; Morales, Javier O. (Frontiers in Cellular and Infection Microbiology, 2021)
Urinary tract infection (UTI) is one of the most common reasons for antibiotic treatment. Nevertheless, uropathogens are steadily becoming resistant to currently available therapies. In this context, nanotechnology emerges as an innovative and promising approach among diverse strategies currently under development. In this review we deeply discuss different nanoparticles (NPs) used in UTI treatment, including organic NPs, nanodiamonds, chemical and green synthesized inorganic NPs, and NPs made of composite materials. In addition, we compare the effects of different NPs against uropathogens in vivo and in vitro and discuss their potential impact the in the near future.